Surgical simulation supplements reproductive endocrinology and infertility fellowship training - Tess Chase, M.D; Divya K. Shah, M.D; J. Preston Parry, M.D; Bala Bhagavath, M.D; Steven R. Lindheim, M.D; John C. Petrozza, M.D; Samantha Pfeifer, M.D; Christina Stetter, B.S; Allen Kunselman, M.A; Stephanie J. Estes, M.D (Elsevier, 2020)
Objective: To assess if a surgical boot camp improves laparoscopic skill among reproduction endocrinology and infertility (REI) fellows and increases fellow desire to incorporate surgical skills into practice and to examine whether fellowship in vitro fertilization (IVF) volume correlates with surgical efficiency. Design: Prospective evaluation. Setting: Simulation Center. Patient(s): Forty REI fellows. Intervention(s): Fellows were timed before and after training in laparoscopic suturing and knot tying and while using virtual simulators. Fellows were surveyed before boot camp on prior experience with IVF and reproductive surgery, and immediately and 1 month after boot camp on their desire to incorporate surgical skills into practice. Main Outcome Measure(s): Efficiency of laparoscopic suturing and knot tying before and after boot camp; likelihood and persistence of incorporating surgical skills into practice immediately and 1 month after boot camp; and correlation between fellowship IVF volume and fellow surgical efficiency. Result(s): Fellows experienced significant improvement in laparoscopic suturing (44 sec), intracorporeal knot tying (82 sec), and extracorporeal knot tying (71 sec). Fellows reported being more likely to incorporate operative hysteroscopy (89%), operative laparoscopy (87%), and laparoscopic suturing (84%) into practice immediately following boot camp with no difference 1 month later. Fifty-four percent of fellows reported being more likely to perform robotic surgery after the boot camp, increasing to 70% 1 month later. There were weak correlations between IVF case volume and efficiency in laparoscopic suturing or hysteroscopic polypectomy (Spearman correlation coefficients, -0.14 and -0.03). Conclusion(s): An intensive surgical boot camp enhances surgical skill among REI fellows.